2022
DOI: 10.1556/004.2022.00019
|View full text |Cite
|
Sign up to set email alerts
|

Annual and seasonal trends in cow's milk quality determined by FT-MIR spectroscopy in Hungary between 2011 and 2020

Abstract: We analysed and monitored the major chemical composition of cow's bulk milk by Fourier transform mid-infrared (FT-MIR) spectroscopy over a 10-year period in the whole territory of Hungary. In addition, the two most important key parameters for milk quality assessment, total bacterial count (TBC) and somatic cell count (SCC) were also followed. Production parameters showed significant seasonal and yearly changes. The overall mean fat, protein, lactose and solids-non-fat (SNF) contents of cow's milk were 3.81%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For instance, in a recent study by Feliciano et al (2023) that looked at the quality of raw milk in hot weather conditions throughout a year, seasonal patterns were noticed, but intriguingly, they were not completely explained by the environmental variables, even though it was possible to predict the samples' protein and fat contents using a partial least squares regression. However, a decrease in dry matter and calorie intake due to thermal stress often results in a loss in milk protein and fat contents; therefore, the influence of seasonal temperature on milk composition is also primarily connected to the cow diet (Heck et al 2009;Lim et al 2021;Kocsis et al 2022). Hickey et al (2006) reported that variations in the composition, due to seasonal milk variability, have a considerable impact on overall cheese processing efficacy and on Cheddar cheese's sensory and volatile properties.…”
Section: Impact Of Seasonality On Milk Composition and Cheesemakingmentioning
confidence: 99%
“…For instance, in a recent study by Feliciano et al (2023) that looked at the quality of raw milk in hot weather conditions throughout a year, seasonal patterns were noticed, but intriguingly, they were not completely explained by the environmental variables, even though it was possible to predict the samples' protein and fat contents using a partial least squares regression. However, a decrease in dry matter and calorie intake due to thermal stress often results in a loss in milk protein and fat contents; therefore, the influence of seasonal temperature on milk composition is also primarily connected to the cow diet (Heck et al 2009;Lim et al 2021;Kocsis et al 2022). Hickey et al (2006) reported that variations in the composition, due to seasonal milk variability, have a considerable impact on overall cheese processing efficacy and on Cheddar cheese's sensory and volatile properties.…”
Section: Impact Of Seasonality On Milk Composition and Cheesemakingmentioning
confidence: 99%
“…195 depending on the season (Auldist et al, 1998;Heck et al, 2009;Salfer et al, 2019;Kocsis et al, 2022). The dairy industry and the quality of milk products are affected directly by changes in raw milk composition (Li et al, 2019;Yener et al, 2021;Jensen, 2022;Kocsis et al, 2022) In natural processes, a variety of gaseous pollutants are released, including greenhouse gases (GHG). However, human activity significantly increases their presence in the environment.…”
Section: ____________________________________________________________...mentioning
confidence: 99%